2014
DOI: 10.1007/s12070-014-0704-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Between Double Layered Repair of Pharyngeal Mucosa Against Routine Single Layered Repair in Cases of “Total Laryngectomy with Partial Pharyngectomy” in Respect To Formation of Pharyngo-cutaneous Fistula

Abstract: Advanced glottic cancer (T3,N? & T4) is usually treated in the majority of centres by total laryngectomy. Carcinoma of the larynx is one of the very few subsets of all cancers which have shown a decrease in the 5 year survival rate and this phenomenon has been attributed to a Pharyngocutaneous fistula is the most common complication after total laryngectomy. Comparative study between double layered repair of pharyngeal mucosa against routine single layered repair in cases of ''total laryngectomy with partial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Avci et al [ 43 ] compared continuous versus interrupted suture using a vertical approach and found a statistically significant difference between PCF rates favoring continuous suture (16% vs. 39%). Shukla et al [ 44 ] compared a single vs. a double-layer suture using the T-shape technique and found a statistically significant difference favoring two-layer suture (PCF rate 12.5% vs. 33.3%). Wang et al [ 45 ] and Saha et al [ 46 ] compared the two-layer suture with a modified technique using the remnant of constrictor muscles as suture reinforcement and found a statistically significant difference favoring the two-layer technique without muscle reinforcement (PCF rate 3% vs. 10% and 0% vs. 27%, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Avci et al [ 43 ] compared continuous versus interrupted suture using a vertical approach and found a statistically significant difference between PCF rates favoring continuous suture (16% vs. 39%). Shukla et al [ 44 ] compared a single vs. a double-layer suture using the T-shape technique and found a statistically significant difference favoring two-layer suture (PCF rate 12.5% vs. 33.3%). Wang et al [ 45 ] and Saha et al [ 46 ] compared the two-layer suture with a modified technique using the remnant of constrictor muscles as suture reinforcement and found a statistically significant difference favoring the two-layer technique without muscle reinforcement (PCF rate 3% vs. 10% and 0% vs. 27%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…We only identified one comparative study specifically evaluating this question, showing that a continuous suture decreases the rate of PCF. Avci et al [ 43 ] found a difference of almost 20% lower rate of PCF with a two-layer suture and, although this is an observational non-RCT, the magnitude of the difference is so high that it should be accepted as conclusive [ 44 ]. Regarding the number of layers the situation was similar: two layers were more effective than a single one [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation